Calderón en su taller: algunas intervenciones en los autógrafos de los autos sacramentales - Arellano, Ignacio (Anuario Calderoniano, 2015)
El artículo examina diversos autógrafos de piezas sacramentales de Calderón, analizando las informaciones que aporta el proceso de escritura, corrección y perfeccionamiento reflejado en los cambios e intervenciones de la mano del poeta sobre sus propios manuscritos, en varias categorías, incluyendo los errores de copia. «Calderón in his Workshop: Remarks on the Autographs of Sacramental Plays» This paper examines some significant autographs of Calderón’s sacramental plays, analyzing the information provided by the process of writing and amendment reflected in the changes and interventions by the own hand of the poet on this manuscripts, in several categories, including the mistakes and slips of the pen. PALABRAS CLAVES / KEYWORDS: Calderón, autógrafos, autos sacramentales, transmisión textual / Calderón, autographs, allegorical plays, textual transmission.